2018
DOI: 10.3390/en11010168
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Flow Paths in 3D Self-Affine Fractures with Lattice Boltzmann Simulations

Abstract: Abstract:In this study, laboratory experiments and simulations have been conducted to investigate single water phase flow through self-affine rough fractures. It is the first time that 3D printing technology is proposed for the application of generating self-affine rough fractures. The experimental setup was designed to measure the water volume by dividing the discharging surface into five sections with equal distances under constant injection flow rates. Water flow through self-affine rough fractures was simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Different flow regimes, e.g., droplet, rivulet, and film flow, can coexist even in controlled settings and are difficult to cast into unified conceptual frameworks (Ghezzehei, 2004). In well-controlled analog percolation experiments, the fracture-specific formation of flow modes and instabilities (Jones et al, 2018;Li et al, 2018) and the role of unsaturated fracture intersections on partitioning behavior has been investigated (e.g., Ji et al, 2006;Kordilla et al, 2017;LaViolette et al, 2003;Nicholl and Glass, 2005;Wood et al, 2002Wood et al, , 2005Wood and Huang, 2015), where the applied flow rate controls the stability of a desired flow regime (Towell and Rothfeld, 1966;Schmuki and Laso, 1990). These studies emphasize the importance of fracture intersections as capillary barriers (until steady-state conditions are established), which may induce pulsating flows and act as important integrators for dispersion and recharge processes.…”
mentioning
confidence: 99%
“…Different flow regimes, e.g., droplet, rivulet, and film flow, can coexist even in controlled settings and are difficult to cast into unified conceptual frameworks (Ghezzehei, 2004). In well-controlled analog percolation experiments, the fracture-specific formation of flow modes and instabilities (Jones et al, 2018;Li et al, 2018) and the role of unsaturated fracture intersections on partitioning behavior has been investigated (e.g., Ji et al, 2006;Kordilla et al, 2017;LaViolette et al, 2003;Nicholl and Glass, 2005;Wood et al, 2002Wood et al, , 2005Wood and Huang, 2015), where the applied flow rate controls the stability of a desired flow regime (Towell and Rothfeld, 1966;Schmuki and Laso, 1990). These studies emphasize the importance of fracture intersections as capillary barriers (until steady-state conditions are established), which may induce pulsating flows and act as important integrators for dispersion and recharge processes.…”
mentioning
confidence: 99%
“…Kishida et al [12] suggested that the applicability of the Reynolds equation is limited to low Re conditions and smooth fracture walls, so that the flow rate and local velocity components perpendicular to the nominal fracture plane are sufficiently low. In order to solve this problem, some researchers [13][14][15] have investigated the role of the aperture length and its spatial variation on the distribution of flow rates along the fracture. They reported that the characterization of fracture geometry, such as mismatch length and fractal dimension, led to the change in flow rates within the fracture, which can be visualized using a transparent fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Another study shows that with the increase of fracture roughness, the eddy volumes become larger and the effective hydraulic conductivities decreases in rough fractures [52]. An experiment has been designed for the investigation of water flow through fractures with rough surfaces that are generated by 3D printing technology and then the experimental results are compared with simulation results from LBM [53].…”
Section: Introductionmentioning
confidence: 99%